Implementasi Model Pembelajaran Kooperatif Tipe TAI untuk Meningkatkan Kompetensi 4C dan Hasil Belajar Siswa pada Mata Pelajaran Skmi Kelas XI TMI 1 SMK Negeri 1 Pariaman - Agusriza Almalik; Yufrizal A; Arwizet K; Delima Yanti Sari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research addresses the low student learning outcomes and the lack of facilitation of 4C competencies (Critical Thinking, Collaboration, Communication, and Creativity) in the Industrial Machine Electrical Systems (SKMI) subject for Grade XI TMI 1 students at SMK Negeri 1 Pariaman. The teacher-centered learning approach has led to passive student participation, low critical thinking, varying academic abilities, and difficulty in connecting theoretical concepts to real-life applications. The aim of this study is to improve students' 4C competencies and learning outcomes through the implementation of the Team Assisted Individualization (TAI) cooperative learning model. Using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, the study was conducted in three cycles: planning, implementation, observation, and reflection. The subjects were 30 students from Grade XI TMI 1. Data collection included learning outcome tests and 4C competency observation sheets, with descriptive and quantitative data analysis. The results showed significant improvements: classical mastery increased from 27% to 90%, average learning scores rose from 67 to 81, and 4C competency mastery improved from 34% (low) to 82% (high). The study concludes that the TAI model effectively enhances both 4C competencies and learning outcomes in SKMI at SMK Negeri 1 Pariaman.